TINJAUAN HUKUM LINGKUNGAN DAN HUKUM KEHUTANAN TERHADAP KERUSAKAN HUTAN DAN LINGKUNGAN PADA IZIN USAHA PEMANFAATAN HASIL HUTAN KAYU (IUPHHK-HA) DALAM HUTAN ALAM PADA HUTAN PRODUKSI - Sularno Sularno (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTThe focal point of this research is to highlight the policy of the Government of the Republic of Indonesia since the New Order era in issuing forestry decisions in the form of Forest Forest Protection Permit (HPH) or Timber Forest Product Utilization Permit in Natural Forest (IUPHHK-HA now) Governments, Local Governments, and forest communities, knowing the very happy IUPHHK-HA activities due to the failure of the forestry environment, types of activities and how to recover damage to the forestry environment. Include constraints and barriers - what unit units, efforts are being made to overcome these obstacles and barriers, and appropriate forms of accountability for forest damage offenders and environmental degradation, as well as the terms and conditions that must be met by IUPHHK-HA legally and legally produced timber products in accordance with the Law and other applicable provisions.The method used is the empirical juridical approach that is the approach done by looking at existing practices in the field. This is done in a straightforward way in the field. In relation to this research with empirical juridical research methods, the authors conducted a study of primary data in the field of environmental management and implementation, on the types of IUPHK-HA activities that often cause environmental damage, the impact of these activities as well as ways - forest destruction recovery, explosive solutions, the efforts made by the Timber Forest Product Utilization Permit (Plantation Forest) in the Natural Forest in Production Forest of PT. Triwiraasta Bharata in West Kutai district of East Kalimantan Province, and a form of accountability for plasma companies undertaking lessons in the forestry environment.The results of this study and study provide an overview of Timber Forest Product Utilization Permit in Natural Forest (IUPHHK-HA) in accordance with its permit are logs, for legal and legal log products in accordance with applicable laws and regulations, the requirements are not small and the time and process is long enough. Unlike some people who imagine that the logging business is the easiest and the fastest because he immediately cuts and sales. Perhaps the assumption that there is a targeted truth is a culprit of illegal loggers or liar pemarakong.The current condition provides an overview divided into the form of IUPHHK-HA which is included in severe and full conditions. There are several things that cause it to happen, among others: forestry regulations are increasingly tight, often fickle, burdensome and get a high price; increasing legal uncertainty and business uncertainty caused by reform euphoria affecting customary land claims, customary rights, ancestral forest claims without a legal basis; reducing standing conditions due to uncontrolled illegal logging behaviors that have occurred in the last 15 (fifteen) years, overlapping of mining land spent in forested areas, international pressures exploiting the issue of forest and environmental degradation.Law Number 41 Year 1999 on Forestry, Law Number 32 Year 2009 on Environmental Protection and Management, Law Number 18 Year 2013 on Prevention and Eradication of Forest Degradation, Instruments and Highlights with correct field application and capable in implementing mandate for the Protection of deforestation and the environment, perhaps only what needs to be improved actually in enforcement and enforcement